ROLE OF СD14 AND CYTOKINE GENE POLYMORPHISM IN CLINICAL FEATURES AND OUTCOMES OF NOSOCOMIAL PNEUMONIA - E. A. Baygosina; V. I. Sovalkin (Медицинская иммунология)
Abstract. This article is devoted to analysis of gene polymorphisms affecting CD14 regulatory molecule, as well as IL-1β, TNFα cytokines and IL-1RN in the patients with nosocomial pneumonias. The influence of single-nucleotide substitution polymorphisms is discussed in terms of clinical severity and outcomes of nosocomial pneumonia. A predisposition for more severe clinical course of pneumonia is revealed in a group of patients with C/Т and Т/Т genotypes of CD14 regulatory molecule. A carriership of –511*Т аllele in the patients’ genotype predisposed for reduced terms of pneumonia evolution, like as development of acute respiratory distress syndrome and more pronounced acute phase response (leukocytosis and high levels of C-reactive protein). IL-RN*2 allele was associated with generally poor outcome, whereas presence of –308 (AG, AA) variant of TNFα polymorphic gene was connected with pulmonary and extrapulmonary complications of nosocomial pneumonia. (Med. Immunol., vol. 10, N 4-5, pp 467-472).